Application of TEACCH method to sharpen life skills in children with autism. - Septianingrum, Putri; Hayyu Erfantinni, Imro’atul; Rochmah, Ainur; Rahimah, Rahimah (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background : The prevalence of autism in Indonesia has risen significantly in recent years, requiring targeted interventions to address developmental challenges. Special education institutions like TKLB River Kids play a crucial role in equipping autistic children with essential life skills to enhance their independence and quality of life. The TEACCH (Treatment and Education of Autistic and Associated Communication Handicapped Children) method has been widely recognized for its structured approach tailored to the unique needs of autistic individuals. This study examines the implementation of the TEACCH method at TKLB River Kids to explore its impact on developing life skills among autistic children.Aim : The study aims to analyze the application of the TEACCH method in honing life skills among autistic children at TKLB River Kids, identifying the influencing factors and the outcomes of this intervention.Method : This qualitative study employed a case study design to deeply explore the implementation of the TEACCH method. Data collection involved a one-month observation, interviews with three teachers and one therapist, and documentation analysis at TKLB River Kids. Triangulation techniques were used to validate the data, and Miles and Huberman's interactive model was applied for analysis.Results : The findings reveal that the TEACCH method, utilizing visual schedules, independent work systems, and structured task organization, significantly improved life skills such as self-care, communication, motor development, and social interaction. Internal factors like children’s motivation and cognitive abilities, as well as external factors including parental support and the availability of visual aids, influenced the program’s success. Improvements in emotional regulation, task completion, and independence were observed, with parents and educators reporting reduced stress and enhanced family dynamics.Conclusion : The structured implementation of the TEACCH method at TKLB River Kids has effectively fostered independence and life skills development in autistic children. The collaborative approach involving schools and families highlights the potential for broader application in special education settings, offering a sustainable model for enhancing the well-being of children with Autism Spectrum Disorder.